CONDICIONES DE VIDA Y SU INCIDENCIA EN LA IDENTIDAD PERSONAL-SOCIAL DE ADLESCENTES NICOYANOS - Moreno, Wagner (1994)
This article shows a brief conceptualization of tbe socloeconomic conditions of Nicoya Guanacaste, which have a significant influence in the young population, specifically their living condltlons, the building of the personal - social identity and obviously their life proyect.